Nilai-Nilai Karya Cipta dan Problematik Perlindungan Hukumnya - M. Syamsudin (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The following essay tries to address some issues related to patent right in Indonesia. It is found out from the study that the conception of patent right is not recognized in Indonesian traditional community. Demands for admitting and respecting the existence of  patent right have to do with the influence of legal ide as from the Schoolor Doctrine of Natural-Law which heavily stresses on human factors and the use of mind which have been familiar and well known'in the system of civil law in European Continents. The conceptof patent right, including its law protection in Indonesia, still faces various obstacles, specially cultural ones.